Farm animal proteomics : Proceedings of the 3rd Managing Committee Meeting and 2nd meeting of working groups 1, 2 & 3 of COST Action FA1002 - Eckersall, David; Almeida, André; Rodrigues, Pedro (Wageningen Academic Publishers, 2012)
Proteomics is a field with growing interest in almost every area of life sciences. Proteomic techniques, along with potential and obtained results have long been key components of biomedical and pharmaceutical research. In agriculture, animal and veterinary research however, use of proteomics is still limited, despite the large number of potential applications. As a result, there is a pressing need for wider use and dissemination of proteomics in animal and veterinary science research. This book meets this need by bridging the gap between experts in the technology of proteomics and those at the forefront of research into many facets of animal physiology and pathophysiology. The book encompasses a wide range of topics: from muscle and meat proteomics to acute phase proteins and proteomics in aquaculture, to name but a few. The book summarily presents the state of the art in farm animal proteomics research in Europe, providing readers with interesting examples of the applications of this set of advanced technologies as well as useful contact details of colleagues with expertise in the field. The book will be of interest to scientists at the cutting edge of animal and veterinary research who are currently, or are considering, analytical investigation and identification of protein in animal tissue and in pathogens in health and disease. Furthermore the book will provide an insight for proteomic specialists in demonstrating the breadth of applications that their technology can have in animal and food research.